2015
DOI: 10.1007/s00775-015-1306-y
|View full text |Cite
|
Sign up to set email alerts
|

Elemental changes in the hippocampal formation following two different formulas of ketogenic diet: an X-ray fluorescence microscopy study

Abstract: The main purpose of the following study was the determination of elemental changes occurring within hippocampal formation as a result of high-fat and carbohydrate-restricted ketogenic diet (KD). To realize it, X-ray fluorescence microscopy was applied for topographic and quantitative analysis of P, S, K, Ca, Fe, Cu, Zn and Se in hippocampal formations taken from rats fed with two different KDs and naive controls. The detailed comparisons were done for sectors 1 and 3 of the Ammon’s, the dentate gyrus and hilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
8
1
Order By: Relevance
“…Although, the content of PUFAs was slightly higher in KD1 comparing to KD2, lower ketogenic ratio KD did not induce significant changes in the unsaturation level of lipids within the hippocampal formation of normal rats [22]. From the other side, such effect was observed for animals treated with KD2 in which the content of unsaturated fatty acids was significantly higher comparing to rats on the standard diet [20]. Therefore, rather the increased hippocampal level of PUFAs than ketone bodies may be linked with the effectiveness of KD in the treatment of epilepsy.…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…Although, the content of PUFAs was slightly higher in KD1 comparing to KD2, lower ketogenic ratio KD did not induce significant changes in the unsaturation level of lipids within the hippocampal formation of normal rats [22]. From the other side, such effect was observed for animals treated with KD2 in which the content of unsaturated fatty acids was significantly higher comparing to rats on the standard diet [20]. Therefore, rather the increased hippocampal level of PUFAs than ketone bodies may be linked with the effectiveness of KD in the treatment of epilepsy.…”
Section: Discussioncontrasting
confidence: 48%
“…The analysis of the influence of KDs 1 and 2 on the elemental composition of normal hippocampal formation was the subject of our previous paper published in JBIC in 2015 [20]. The results presented there showed that KD induced significant elemental changes in the particular areas of hippocampal formation.…”
Section: Influence Of Kds On the Elemental Composition Of Normal Hippmentioning
confidence: 79%
See 3 more Smart Citations